Pengaruh Lumpur Laut Cair dan Pupuk Kotoran Sapi Terhadap Pertumbuhan dan Hasil Bawang Merah di Tanah Gambut - Tatang Abdurrahman; Radian Radian (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2017)
The objective of the research to know the effect liquid sediment coastal and cow manure on the growth and yield of shallot on peat soil and to know the best dosage can be increased on the yield of shallot. Research conducted at the research field of Faculty of Agriculture, the University of Tanjungpura on April to June 2016, using a completely randomized design factorial with two factors and each treatment combination was replicated three times. The first factor was LLC concentration levels (0.3; 0.6; 0.9 L plant-1). The second factor was cattle manure dosages (25; 50; 75 g plant-1). The research showed that there was an interaction between liquid sediment coastal and cow manure significantly improved the number of tillers, number of bulbs, and fresh weight of shallot. However, there was an interaction between liquid sediment coastal and cow manure and also the effect each treatment not significantly to plant height of shallot. The treatment of liquid sediment coastal 0,6 L plant-1 and cow manure 75 g plant-1 can improve the yield of shallot on peat soil.